Rights and Duties in Menkiti: A Response to Masaka's Objection of Menkiti. Issue 159 (1st July 2019) - Nyirenda, Vitumbiko
Abstract : Dennis Masaka argues that individuals have rights outside those conferred by the community. The argument is a critique to Ifeanyi Menkiti's view of personhood. He argues that Menkiti uses the word person and personhood as synonymous. Masaka makes a distinction between the two, where person is an ontological concept, and personhood is a normative concept. For Masaka, individuals have rights by virtue of being persons and not personhood. My approach to the paper is therapeutic. I argue that Masaka misinterprets Menkiti's views. I argue that Menkiti does not allocate rights in his idea of personhood and as something conferred by the community as proposed by Masaka. This implies that Masaka's view is not radically different from Menkiti's.